Finite Element Analysis of Voided Reinforced Concrete Slabs Enhanced by GFRP Sheets under Monotonic and Repeated Loads (Journal of Engineering, 2024)
Six (1000*1000 mm2) slab specimens were cast and tested as two-way simply supported slabs previously (three under monotonic loading and three under repeated loading) are used in this research. The tested specimens consist of one solid slab and two voided slabs with the following variables (type of slab (solid and voided), presence of steel fibers (0% and 1%), and the presence of GFRP layers). This paper presents the results of tested slabs and the 3D-Nonlinear finite element (ABAQUS program) is proposed to verify the tested slabs under monotonic and repeated loading. The process of modeling the structure components of the tested slabs will be discussed in detail, including the creation of the parts, model material properties, surface interaction, loading method, boundary conditions, and meshing. Then, the experimental findings will be compared to the proposed FE models. A parametric study with new variables has been investigated that affect the behavior of reinforced concrete slabs and is not implemented in the experimental part of this study. These specimens are divided into two groups according to the nature of loading as in the experimental work. The created finite element models can accurately reflect the test results with an acceptable degree of difference in deflection and ultimate load by 10%. The crack patterns obtained using finite element models for the investigated specimens under monotonic and repeated loading are extremely similar to the crack patterns observed in the experimental work.